HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR SISWA KELAS KHUSUS OLAHRAGA - Valentino, Ricky Ferrari; Ardian, Andy (STKIP Pasundan, 2017)
Educational goals can not be separated from academic goals. However, in special sports class students academic achievement actually becomes marginalized compared to non-academic achievements. This study aims to determine the relationship between emotional intelligence and student achievement in special sports classes at SMAN 1 Ciparay. This study is a correlation description study using two types of variables consisting of one independent variable, emotional intelligence and one dependent variable, namely learning achievement. This study uses total sampling, so with this study took a sample of one class of special sports class students in SMA Negeri 1 Ciparay, namely class XI - 11 with a total of 40 students. The instruments used were Questionnaire and student report cards. The method used to analyze the data is the significance test (significance) of the correlation coefficient. The results of the analysis of the research data showed a correlation coefficient of (0.369) then Ha was accepted and Ho was rejected. The conclusion of this study is that there is a relationship between emotional intelligence and learning achievement in special sports class students at SMAN 1 Ciparay.